The Relative Activation Energy of Food Materials: Important Parameters to Describe Drying Kinetics. Issue 8 (2nd August 2016) - Putranto, Aditya; Chen, Xiao Dong
Abstract : An effective drying model should be accurate and require a small number of experiments to generate the parameters. The relative activation energy of various food materials, important drying kinetic properties used in the reaction engineering approach, is evaluated and summarized. The reaction engineering approach is then implemented to model the global and local drying rates of food materials. By using the relative activation energy, the reaction engineering approach describes the ( R 2 higher than 0.99) global drying rate of food materials well. The reaction engineering approach can be coupled with a set of equations of conservation of heat and mass transfer to model the local drying rate of food materials. The relative activation energy is indeed proven to be accurate to model the local drying rate. While the predictions are accurate, the reaction engineering approach is very effective in generating the drying parameters since the relative activation energy can be generated from one accurate drying run. Different drying conditions of the same material with similar initial moisture content would result in the similar relative activation energies. The drying kinetics parameters generated here are readily used for design of new equipment, evaluating the performance of existing dryers, and monitoring the product quality.